FEATURES OF THE CLINICAL COURSE OF CAVERNOUS MALFORMATIONS OF THE BRAIN IN CHILDREN - Rakhimov I.I; Karimov B.A. (Scholar Express Journals, 2022)
Cavernous malformations (CM, cavernomas, cavernous angiomas) of central nervous system represent one of the vascular malformations options, which may form in various locations brain and spinal cord. The spectrum of clinical manifestations of this pathology quite wide - from asymptomatic carriage to severe rebleeding leading to disability or death of the patient. Thanks to ubiquity and technical improvement of modern neuroimaging methods, cavernous malformations of various parts of CNS are found more and more often, and the flow of patients to neurologists and neurosurgeons with this diagnosis, constantly increases. However, cavernomas remain rare disease, diversity of its clinical manifestations and course, complicates right choice of patient management, especially in small neurosurgical departments, with not enough sufficient experience in the treatment of this pathology.
Keywords: Cavernous malformations; cavernomas; children; electroencephalography